2014
DOI: 10.1002/jcb.24708
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Pathway in Osteosarcoma, from Oncogenic to Therapeutic

Abstract: Osteosarcoma is the most common malignant bone tumor in children and adolescents. Although pathologic characteristics of this disease are clear and well established, much remains to be understood about this tumor, particularly at the molecular signaling level. Secreted signaling molecules of the Wnt family have been widely investigated and found to play a central role in controlling embryonic bone development, bone mass, and postnatal bone regeneration. A variety of studies also suggest that Wnt signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 51 publications
4
73
0
1
Order By: Relevance
“…GO terms related to translation (e.g., cytoplasmic translation) were also enriched in OS genes. In line with previous studies, several pathways, such as mTOR signaling pathway (ranked 5th) (29,30), Hippo signaling pathway (ranked 9th) (31), PI3K-Akt signaling pathway (ranked 10th) (30,32), MAPK signaling pathway (ranked 11th) (33), Wnt signaling pathway (ranked 22nd) (34,35), p53 signaling pathway (ranked 24th) (36–38), and TGF-β signaling pathway (ranked 27th) (38,39), were enriched in OS genes. In addition, several cancer-related pathways were identified, such as Pathways in cancer, Proteoglycans in cancer, central carbon metabolism in cancer, and transcriptional misregulation in cancer.…”
Section: Resultssupporting
confidence: 88%
“…GO terms related to translation (e.g., cytoplasmic translation) were also enriched in OS genes. In line with previous studies, several pathways, such as mTOR signaling pathway (ranked 5th) (29,30), Hippo signaling pathway (ranked 9th) (31), PI3K-Akt signaling pathway (ranked 10th) (30,32), MAPK signaling pathway (ranked 11th) (33), Wnt signaling pathway (ranked 22nd) (34,35), p53 signaling pathway (ranked 24th) (36–38), and TGF-β signaling pathway (ranked 27th) (38,39), were enriched in OS genes. In addition, several cancer-related pathways were identified, such as Pathways in cancer, Proteoglycans in cancer, central carbon metabolism in cancer, and transcriptional misregulation in cancer.…”
Section: Resultssupporting
confidence: 88%
“…The role of Wnt signaling in sarcoma biology remains controversial, with some studies suggesting an oncogenic role for this pathway, and other studies supporting an anti-tumorigenic role [26, 27]. Our work directly addresses this controversy.…”
Section: Discussionmentioning
confidence: 88%
“…Other key pathways that regulate cell adhesion, migration, proliferation and survival were downregulated, and have been associated with numerous tumors, including breast and thyroid carcinoma (26). The p53 signaling pathway was demonstrated to serve a pivotal role by forming a complex with its target genes to suppress tumorigenesis (27), and the Wnt signaling pathway, which is a complex network of protein-protein interactions and a major pathway involved in cancer development and embryogenesis, have been reported to be abnormally regulated in a variety of tumors (28)(29)(30)(31). Amongst the pathways associated with the differentially expressed genes in the present study, 6 genes identified to have previously been directly associated with colorectal cancer: T-cell-specific transcription factor 1 (TCF7) (32), cyclin D1 (CCND1) (33), tyrosin-protein kinase met (MET) (34), lymphoid enhancer binding factor 1 (LEF1) (35), axin 2 (AXIN2) (36) and MYC (37).…”
Section: Discussionmentioning
confidence: 99%